Hyperuricemia and Proteinuria in Type 2 Diabetic Patients - Haryandini, Fatya Annisa; Rostini, Tiene (Althea Medical Journal, 2015)
Â Â Â Background: Type 2 diabetes mellitus is a metabolic disorder that has diabetic nephropathy as a complication characterized by proteinuria. When type 2 diabetic patientâs kidney is damaged, hyperuricemia occurs. This study evaluated the correlation of serum uric acid and proteinuria levels in type 2 diabetic patients from outpatient Endocrine clinic at Dr. Hasan Sadikin General Hospital from January to December 2011.Methods: In a cross-sectional study of 125 patients (55 male and 70 female) with type 2 diabetes mellitus, the data of serum uric acid, fasting plasma glucose, 2-h post oral glucose load plasma glucose, serum high-density lipoprotein cholesterol, serum trygliceride, and proteinuria levels were accessed from the medical record. Spearman test was used to calculate the correlation of serum uric acid and proteinuria levels. The research used secondary data taken from medical recordsÂ  of patients diagnosed with T2DMÂ  from outpatient Endocrine clinic of Internal Medicine Department at Dr. Hasan Sadikin General Hospital Bandung who had alaboratory examination at Department of Clinical Pathology of Dr. Hasan Sadikin General Hospital Bandung from January to December 2011.Results: The mean age of the type 2 diabetic patients was 61.5Â±9.2 years old, with mean serum uric acid level of 6.2Â±1,8 mg/dl, of whom 52.8% had microalbuminuric and 4.8% had proteinuria. In type 2 diabetic patients, serum uric acid level correlated positively (r=0.273) with proteinuria (p=0.002).Conclusions: Higher serum uric acid levels associated significantly positive with a greater probability of proteinuria in type 2 diabetic patients, indicating a potential marker for disease severity.Keywords: Proteinuria, type 2 diabetes mellitus, uric acidDOI: 10.15850/amj.v2n1.430Â